The two-pore domain potassium channel, TWIK-1, has a role in the regulation of heart rate and atrial size. (August 2016) - Christensen, Alex Hørby; Chatelain, Franck C.; Huttner, Inken G.; Olesen, Morten Salling; Soka, Magdalena; Feliciangeli, Sylvain; Horvat, Claire; Santiago, Celine F.; Vandenberg, Jamie I.; Schmitt, Nicole; Olesen, Søren-Peter; Lesage, Florian; et al.
Abstract: The two-pore domain potassium (K + ) channel TWIK-1 (or K2P 1.1) contributes to background K + conductance in diverse cell types. TWIK-1, encoded by the KCNK1 gene, is present in the human heart with robust expression in the atria, however its physiological significance is unknown. To evaluate the cardiac effects of TWIK-1 deficiency, we studied zebrafish embryos after knockdown of the two KCNK1 orthologues, kcnk1a and kcnk1b . Knockdown of kcnk1a or kcnk1b individually caused bradycardia and atrial dilation (p < 0.001 vs. controls), while ventricular stroke volume was preserved. Combined knockdown of both kcnk1a and kcnk1b resulted in a more severe phenotype, which was partially reversed by co-injection of wild-type human KCNK1 mRNA, but not by a dominant negative variant of human KCNK1 mRNA. To determine whether genetic variants in KCNK1 might cause atrial fibrillation (AF), we sequenced protein-coding regions in two independent cohorts of patients (373 subjects) and identified three non-synonymous variants, p.R171H, p.I198M and p.G236S, that were all located in highly conserved amino acid residues. In transfected mammalian cells, zebrafish and wild-type human TWIK-1 channels had a similar cellular distribution with predominant localization in the endosomal compartment. Two-electrode voltage-clamp experiments using Xenopus oocytes showed that both zebrafish and wild-type human TWIK-1 channels produced K + currents that are sensitive to external K + concentration as well as acidic pH. There were no effects of the three KCNK1 variants on cellular localization, current amplitude or reversal potential at pH 7.4 or pH 6. Our data indicate that TWIK-1 has a highly conserved role in cardiac function and is required for normal heart rate and atrial morphology. Despite the functional importance of TWIK-1 in the atrium, genetic variation in KCNK1 is not a common primary cause of human AF. Highlights: TWIK-1 has a conserved role as a determinant of atrial function. Zebrafish and human TWIK-1 channels produce similar K + currents. TWIK-1 knockdown in zebrafish embryos results in bradycardia and atrial dilatation. KCNK1 variants are not a common primary cause of human atrial fibrillation.